O olhar humanista cultural sobre as percepções e representações dos povos ribeirinhos do Formate - Pereira, Ernandes de Oliveira (2011)
The world is complex, dynamic and unpredictable. This is the world lived by people. The space is no longer merely a stage of economic developments, social, cultural and natural to make the space experienced by men. This work aims to understand the places lived, the people bordering the format. Their perceptions and representations are the main object of study. From the analysis of narratives of residents, under the theoretical principles of humanistic cultural geography, supported by phenomenology, sanctified by Edmund Husserl, aims to understand the world views of the river dwellers. Analysis of these feelings of fear, spaciousness and the hope of a better place emerge each river flooding Format. From this fact, we identified two worldviews, two notions of place, one of the riverine communities and other representatives of the popular environmental movement. Both have in common knowledge of common sense, drawn from the experiences of everyday life, often ignored by the scientific thought. The humanistic approach is more a cultural ability to understand the world, not as a substitute for other perspectives of geographic thought, but as a complement to the geographer has multiple tools to understand the multiplicity of the world.